International management of hazardous wastes - Kummer, Katharina (Clarendon Press,Oxford University Press, 1999)
The book analyses the key treaties and other international legal rules on the control of transboundary movements of hazardous wastes. It identifies inconsistencies, gaps, and overlaps, and proposes ways to build a comprehensive global regulatory system for the management of hazardous wastes by harmonizing relevant international legal rules